Depression and Anxiety in Pediatric Patients with Beckwith–Wiedemann Syndrome: A Pilot Study - Grazia D’Onofrio; Annalisa Mastromatteo; Andrea Di Francesco; Antonio Izzi; Vincenzo Marchello; Aldo Manuali; Andreaserena Recchia; Maria Pia Tonti; Maria Lazzarina Russo; Maria Pia Affatato; Alessandra Rossato; Cecilia Giuntoli; et al. (Children, 2024)
The study’s aim was to determine the prevalence of depression and anxiety in children with Beckwith–Wiedemann syndrome (BWS) and their effects on social relationships and family acceptance. The Pediatric Symptom Checklist—35 items (PSC-35), Screen for Child Anxiety Related Emotional Disorders (SCARED), and the Vineland Adaptive Behavior Scale Second Edition (VABS-II) were administered to the children. The parental Acceptance Rejection/Control Questionnaire (PARQ/Control) and Zarit Burden Inventory (ZBI) were administered to parents. In total, 6 patients and 10 parents were included. Patients showed a significant presence of internalizing behavior in PSC-35 (mean, 7.66 ± 3.67), anxiety symptoms (SCARED: mean, 46.33 ± 17.50) and socialization difficulties (mean, 90.83 ± 10.09). Parents reported a perceived good acceptance (mean, 56.33 ± 1.03) and a moderate control (mean, 24.17 ± 1.83), but the burden level was ranked moderate to severe (mean, 59.33 ± 16.78). It was found that the severity of the burden level reported by parents was related to internalizing behavior (OR = 2.000; 95% CI = 0.479–3.521; p = 0.022) and anxiety symptoms (SCARED total score: OR = 3.000; 95% CI = 1.479–4.521; p = 0.005) of children. During psychological counseling in the context of BWS treatment, it is important to identify specific resources that can support patients and families in dealing with stress and identify any critical areas that could hinder the adaptation process.